Petrogenesis and origin of the Upper Jurassic-Lower Cretaceous magmatism in Central High Atlas (Morocco): Major, trace element and isotopic (Sr-Nd) constraints. (January 2018) - Essaifi, Abderrahim; Zayane, Rachid
Abstract: During an uplift phase, which lasted ca. 40 Ma, from the Late Jurassic (165 Ma) to the Early Cretaceous (125 Ma), transitional to moderately alkaline magmatic series were emplaced in the Central High Atlas. The corresponding magmatic products include basaltic lava flows erupted within wide synclines and intrusive complexes composed of layered mafic intrusions and monzonitic to syenitic dykes emplaced along narrow anticlinal ridges. The igneous rock sequence within the intrusive complexes is composed of troctolites, olivine-gabbros, oxide-gabbros, monzonites and syenites. The chemical compositions of the various intrusive rocks can be accounted for by crystal accumulation, fractional crystallization and post-magmatic remobilization. The evolution from the troctolites to the syenites was mainly controlled by a fractional crystallization process marked by early fractionation of olivine, plagioclase and clinopyroxene, followed by separation of biotite, amphibole, apatite, and Ti-magnetite. Hydrothermal activity associated with emplacement of the intrusions within the Jurassic limestones modified the elemental and the Sr isotopic composition of the hydrothermally altered rocks In particular the monzonitic to syenitic dykes underwent an alkali metasomatism marked by depletion in K and Rb and enrichment in Na and Sr. As a result, their Sr isotopic composition was shifted towards higher initial Sr isotopic ratios (0.7067–0.7075) with respect to the associated gabbros (0.7036–0.7046). On the contrary, the Nd isotopic compositions were preserved from isotope exchange with the limestones and vary in a similar range to those of the gabbros (+1.6 < εNdi < +4.1). The isotopic and the trace element ratios of the uncontaminated samples were used to constrain the source characteristics of this magmatism. The Sr-Nd isotopic data and the incompatible element ratios (e.g. La/Nb, Zr/Nb, Th/U, Ce/Pb) are consistent with generation from an enriched upper mantle similar to an ocean island basalt source. Melting of the subcontinental metasomatized lithosphere is tentatively related to small-scale shallow mantle upwelling and asthenospheric uprise at the triple junction between the western High Atlas, the Middle Atlas and the eastern High Atlas domains during a period of relative tectonic quiescence. Highlights: Mesozoic transitional to moderately alkaline magmatism emplaced in the High Atlas. Fractional crystallization allowed evolution from troctolites to oxide-gabbros and syenites. Alkali metasomatism modified the Sr isotopic composition of the syenites. The Sr-Nd isotopic composition of uncontaminated gabbros indicate an enriched upper mantle. The enriched upper mantle signature is related to pre-Mesozoic geodynamic processes.